Thermal management challenges for HEA–FUTPRINT 50 - Affonso Jr., Walter; Gandolfi, Ricardo; Nunes dos Reis, Ricardo Jose; da Silva, Carlos Roberto Ilário; Rodio, Nicolas; Kipouros, Timoleon; Laskaridis, Panagiotis; Chekin, Andrei; Ravikovich, Yury; Ivanov, Nikolay; Ponyaev, Leonid; Holobtsev, Dmitry (IOP Publishing, 2021)
Electric and Hybrid-Electric Aircraft (HEA) incorporate new systems, which demand an integration level higher than classical propulsion architectures systems do. High power electrical motors, converters, batteries or fuel cells, and distributed propulsion, all introduce new kinds of heat sources and dynamics that have to be accounted for and regulated. The latent opportunity to explore synergies among these systems requires the development of new models and their coupling with multi-disciplinary design optimization (MDO) toolchains. Also, an understanding of the implications into aircraft operations and trade-offs are critical to evaluate and validate gains at the aircraft level. This paper provides a definition of thermal management and functions of thermal management system (TMS) in aircraft, HEA thermal management challenges, main opportunities, conclusions and the way forward. A discussion of road ahead, regarding development of capabilities to support the design of TMS will be brought to the fore along the project, showcasing the open approach of FUTPRINT50 to be driven by open collaboration in order to accelerate the entry into service of this type of aircraft.